A penta‐band microstrip slot antenna for S‐, C‐ and X‐band applications - Muhammad Asad Rahman; MD Shahidul Islam; MD Shakil Hossain; Maodudul Hasan; Eisuke Nishiyama; Ichihiko Toyoda (Electronics Letters, 2023)
Abstract This letter presents a compact penta‐band microstrip slot antenna. The proposed antenna comprises a microstrip feed line on the top plane, a polytetrafluoroethylene (PTFE) substrate, and a slotted ground plane. Different shapes of slots and two pairs of horizontal strips on the ground are introduced to achieve five frequency bands. A prototype is fabricated and measured to demonstrate the validity of the design. According to the measured result, the fabricated antenna can operate at five operating frequencies with an impedance bandwidth of 2.41–2.55 GHz (5.65%) for Bluetooth and WLAN, 3.31–3.58 GHz (8.14%) for WiMAX and Sub‐6 GHz 5G applications, 4.52–4.76 GHz (5.17%) for radiometry, 5.10–6.20 GHz (19.47%) for WLAN and ITS, and 10.14–12.40 GHz (20.10%) for radar applications. Moreover, the proposed antenna shows a bi‐directional radiation pattern at each operating band.